Integration of Socio-Ecological Systems in Urban Forest Agroecosystem Management for Sustainable Tourism - Husnul Jannah; Wahyu Astiko (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Urban agroecosystem management faces pressures from urbanization, environmental degradation, and weak integration policies, resulting in a decline in the quality of ecosystem services. Sectoral approaches have not been able to systematically integrate ecological and social dimensions. This study aims to formulate a conceptual model for urban agroecosystem management based on the Socio-Ecological Systems (SES) framework as an integrative approach to sustainability. The method used is a systematic literature review of international publications in the last five years related to ecosystem services, green infrastructure, peri-urban agroecology, and collaborative governance. A total of 100 scientific articles were obtained through the search process, and after going through the screening process, a total of 15 articles were obtained as the main material for the scientific literature process in this study. The analysis shows that vegetation and biodiversity are ecological ecosystems that produce regulatory, provisioning, and cultural ecosystem services. These benefits contribute to improving environmental quality and community well-being. Adaptive governance, community participation, and ecosystem-based integration policies significantly influence the ecosystem system, creating positive feedback mechanisms. The developed conceptual model emphasizes the interconnectedness of biophysical and social components in building resilient and sustainable urban agroecosystems. This study proposes a new conceptual model based on socio-ecological systems that integrates biophysical, social, and tourism dimensions in urban forest agroecosystems by placing tourism experience as the main mediating variable in shaping the desire feedback mechanism.